2019
DOI: 10.1016/j.revmic.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

First record of Permo-Triassic palynomorphs of the N’Condédzi sub-basin, Moatize-Minjova Coal Basin, Karoo Supergroup, Mozambique

Abstract: Permian-Triassic ages have been identified for the first time in the Karoo Supergroup of the N'Condédzi sub-basin, Moatize-Minjova Coal Basin, Mozambique. This transition was identified in a coal exploration borehole that penetrated the Matinde and Cádzi formations. The top of the Matinde Formation is dated latest Permian (Lopingian), and the Cádzi Formation is attributed to Triassic based on palynostratigraphy. The Lopingian age is established by the identification of three palyno-assemblages: Assemblage L1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The second structural trend is approximately NW‐SE trending and is mainly marked by the Shire valley at the edge of the Lurio belt (Figure 1) (Castaing, 1991), becoming N‐S along the southern part of the Lebombo Monocline. Interestingly, both trends were reactivated locally during (a) the Permian‐Triassic time as evidenced by the presence of Karoo rifts associated with the Karoo Supergroup (e.g., Castaing, 1991; Catuneanu et al., 2005; Galasso et al., 2019; Watkeys, 2002) and (b) the Early to Middle Jurassic (e.g., Cox, 1992; Castaing, 1991) as evidenced by the presence of a large igneous province (LIP) and various set of faults which locally controlled the LIP emplacement (ca. 180 Ma, Duncan et al., 1997; Riley et al., 2004; Jourdan et al., 2007; Svensen et al., 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…The second structural trend is approximately NW‐SE trending and is mainly marked by the Shire valley at the edge of the Lurio belt (Figure 1) (Castaing, 1991), becoming N‐S along the southern part of the Lebombo Monocline. Interestingly, both trends were reactivated locally during (a) the Permian‐Triassic time as evidenced by the presence of Karoo rifts associated with the Karoo Supergroup (e.g., Castaing, 1991; Catuneanu et al., 2005; Galasso et al., 2019; Watkeys, 2002) and (b) the Early to Middle Jurassic (e.g., Cox, 1992; Castaing, 1991) as evidenced by the presence of a large igneous province (LIP) and various set of faults which locally controlled the LIP emplacement (ca. 180 Ma, Duncan et al., 1997; Riley et al., 2004; Jourdan et al., 2007; Svensen et al., 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…It should be noted that both species usually occur together in assemblages of the PTB interval (e.g. Cirilli et al 1998, Galasso et al 2019, Hermann et al 2012) and Olenekian (e.g. Rossi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Later, Galasso et al (2019) identified two Early Triassic assemblages in the N'Condédzi Sub-basin (Mozambique) similar to the La Veteada Formation palynofloras. The Assemblage T1 is defined by the FO of Densoisporites nejburgii of Induan age, and Assemblage T2 is marked by the FO of Platysaccus queenslandi and assigned to the Olenekian.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative spore UV Fluorescence colors are an indicator of thermal maturity of OM useful for low-rank rocks up to the beginning of the oil window (R o ≈ 1.35-1.50%; e.g., [38,[123][124][125][126][127][128]. Fluorescence microscopy is used to evaluate the level of maturation of a rock from fluorescence colors and spectra [126,129,130].…”
Section: Spore Uv Fluorescencementioning
confidence: 99%